Review of Europiella Reuter (Hemiptera: Heteroptera: Miridae: Phylinae: Phylini) from Korea, with a description of a new genus - Duwal, Ram Keshari; Jung, Sunghoon; Lee, Seunghwan (Zootaxa, 2014)
Five species of Europiella (Phylinae: Phylini) including three newly reported species, E. artemisiae (Becker, 1864), E. kiritshenkoi Kulik, 1975, and E. miyamotoi (Kerzhner, 1988), are recognized for the first time from Korea, and Europiella albipennis (Fallén, 1829) is removed from the Korean list. A new genus Europiellomorpha Duwal n. gen., is proposed to accommodate Plagioganthus lividellus (Kerzhner, 1979) (= Europiella lividellus). A key to the Korean species of Europiella, diagnosis, and descriptions of both male and female genitalia are provided.